Hsa-miR-7974 Suppresses Epstein-Barr Virus Reactivation by Directly Targeting BZLF1 and BRLF1 - Haotian Li; Hui Wang; Jiao Wang; Xuexin Lu; Jieqiong Zhang; Mingming Wang; Dongbo Yu; Ying Li; Shiwen Wang (Viruses)
Epstein-Barr virus (EBV) reactivation, a key factor in Epstein-Barr virus (EBV)-associated malignancies, is regulated by specific cellular microRNAs (miRNAs). This study investigated the role of Hsa-miR-7974 (miR-7974) in this process. miRNA sequencing revealed significant downregulation of miR-7974 in reactivated EBV-positive cell lines (Raji and C666-1). Bioinformatics prediction and dual-luciferase assays confirmed the direct targeting of the EBV immediate-early gene BRLF1 by miR-7974. Furthermore, miR-7974 mimics suppressed, whereas inhibitors increased, the expression of key EBV lytic genes (BZLF1, BRLF1, and BMRF1) and the viral load, as validated by RT-qPCR. Bioinformatics analyses revealed the involvement of miR-7974 in cellular pathways such as membrane dynamics and signal transduction (MAPK, NF-κB, and IL-10), and its association with Hodgkin’s lymphoma, leukemia, and nasopharyngeal neoplasms. These findings establish that miR-7974 functions as a crucial negative regulator of EBV reactivation by directly targeting BRLF1, highlighting its potential significance in the pathogenesis of EBV-associated malignancies.